Damage to concrete structures - De Schutter, Geert (CRC Press, 2013)
Unlike the more specialist books which deal with diagnosis techniques or non-destructive testing, with repair and strengthening of concrete structures or with specific degradation mechanisms such as sulfate attack or alkali-silica reaction, this book describes and explains the different types of damage to concrete structures comprehensively. It is written as a textbook for undergraduate and masters students, and is also helpful to practitioners such as design engineers, architects or consultants.